REGIONAL BUSINESS CYCLES AND INCOME CONVERGENCE IN US - Hasan Engin Duran (European Regional Science Association (ERSA), 2010)
Since early 90s, the issue of income convergence across regions has been widely discussed in a number of papers, both looking at long-term tendencies and trying to establish the role played by several socio-economic determinants. Much less attention has instead been devoted to the analysis of short-run convergence dynamics and the relationship with national business cycle. In the few papers that tackle this issue it is generally found that income disparities follow a pro-cyclical pattern, increasing during times of national expansions and decreasing in recessions. However, two important aspects have not yet been adequately studied in this specific area of research. First, is the relationship between national business cycle and regional income disparities linear or, rather, nonlinear. Second, what are the mechanisms and economic reasons behind the cyclical evolution of regional income disparities? And, more specifically, is the cyclical evolution a consequence of difference in the timing with which the business cycle is felt in regional economies or, alternatively, is it mainly motivated by the presence of size differences across local cyclical swings. In the present paper, we investigate the above issues using a combination of established and newly developed nonparametric tools applied to data on the states of US between 1969 and 2008.
Keywords: 330; Cyclical Regional Disparities; Regional Business Cycles; Income Convergence